Free iron catalyzes oxidative damage to hematopoietic cells/mesenchymal stem cells in vitro and suppresses hematopoiesis in iron overload patients. (15th July 2013) - Lu, Wenyi; Zhao, Mingfeng; Rajbhandary, Sajin; Xie, Fang; Chai, Xiao; Mu, Juan; Meng, Juanxia; Liu, Yongjun; Jiang, Yan; Xu, Xinnv; Meng, Aimin
Abstract Objectives Transfusional iron overload is of major concern in hematological disease. Iron‐overload‐related dyserythropoiesis and reactive oxygen species (ROS)‐related damage to hematopoietic stem cell (HSC) function are major setbacks in treatment for such disorders. We therefore aim to investigate the effect of iron overload on hematopoiesis in the patients and explore the role of ROS in iron‐induced oxidative damage in hematopoietic cells and microenvironment in vitro. Patients and methods The hematopoietic colony‐forming capacity and ROS level of bone marrow cells were tested before and after iron chelation therapy. In vitro, we first established an iron overload model of bone marrow mononuclear cells (BMMNC) and umbilical cord‐derived mesenchymal stem cells (UC‐MSC). ROS level, cell cycle, and apoptosis were measured by FACS. Function of cells was individually studied by Colony‐forming cell (CFC) assay and co‐culture system. Finally, ROS‐related signaling pathway was also detected by Western blot. Results After administering deferoxamine (DFO), reduced blood transfusion, increased neutrophil, increased platelet, and improved pancytopenia were observed in 76.9%, 46.2%, 26.9%, and 15.4% of the patients, respectively. Furthermore, the colony‐forming capacity of BMMNC from iron overload patient was deficient, and ROS level was higher, which were partially recovered following iron chelation therapy. In vitro, exposure of BMMNC to ferric ammonium citrate (FAC) for 24 h decreased the ratio of CD34+ cell from 0.91 ± 0.12% to 0.39 ± 0.07%. Excessive iron could also induce apoptosis, arrest cell cycle, and decrease function of BMMNC and UC‐MSC, which was accompanied by increased ROS level and stimulated p38MAPK, p53 signaling pathway. More importantly, N‐acetyl‐L‐cysteine (NAC) or DFO could partially attenuate cell injury and inhibit the signaling pathway induced by excessive iron. Conclusions Our study shows that iron overload injures the hematopoiesis by damaging hematopoietic cell and hematopoietic microenvironment, which is mediated by ROS‐related signaling proteins.